Interactive Effects of Dietary Fat and APOE Genotype on Peripheral Amyloid-Beta: Implications for Alzheimer’s Disease Risk - D'Alonzo, Zachary John (Curtin University, 2025)
Two main risk factors for Alzheimer’s Disease are the APOE4 gene and a diet high in saturated fat. Additionally, the protein amyloid-beta is a primary pathological characteristic of Alzheimer’s Disease. This thesis demonstrates a vascular axis of Alzheimer’s Disease risk. Following a high-fat meal, humans exhibited elevated levels of amyloid-beta in the blood, with a further increase observed in individuals carrying the APOE4 gene. Notably, this elevation was more pronounced after the consumption of saturated fats compared to unsaturated fats.